Love stories of World War II [large type] - King, Larry, 1933-2021- (Random House Large Print, 2001)
Shares the stories of fifty couples who met and fell in love during World War II, offering a view of the personal side of the wartime experience and the legacy of relationships forged in the midst of tragedy.